Topical Application of Cell-Penetrating Peptide Modified Anti-VEGF Drug Alleviated Choroidal Neovascularization in Mice - Hu W; Cai W; Wu Y; Ren C; Yu D; Li T; Shen T; Xu D; Yu J (International Journal of Nanomedicine, 2024)
Weinan Hu,* Wenting Cai,* Yan Wu, Chengda Ren, Donghui Yu, Tingting Li, Tianyi Shen, Ding Xu, Jing Yu Department of Ophthalmology, Shanghai Tenth People’s Hospital, Tongji University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ding Xu; Jing Yu, Email 15821885240@163.com; dryujing@aliyun.comBackground: Age-related macular degeneration (AMD) stands as the foremost cause of irreversible central vision impairment, marked by choroidal neovascularization (CNV). The prevailing clinical approach to AMD treatment relies on intravitreal injections of anti-vascular endothelial growth factor (VEGF) drugs. However, this method is encumbered by diverse complications, prompting exploration of non-invasive alternatives such as ocular administration via eye drops for anti-VEGF therapy.Methods: Two complexes, 5-FITC-CPP-Ranibizumab (5-FCR) and 5-FITC-CPP-Conbercept (5-FCC), were synthesized by incorporating the anti-VEGF drugs Ranibizumab (RBZ) or Conbercept (CBC) with cell-penetrating peptide (CPP). Circular dichroism spectrum (CD) facilitated complexes characterization. Eye drops was utilized to address laser-induced CNV in mice. Fluorescein fundus angiography (FFA) observe the CNV lesion, while FITC-dextran and IB4 dual fluorescent staining, along with hematoxylin-eosin (HE) staining, assessed in lesion size. Tissue immunofluorescence examined CD31 and VEGF expression in choroidal/retinal pigment epithelial (RPE) tissues. Biocompatibility and biosafety of 5-FCR and 5-FCC was evaluated through histological examination of various organs or cell experiments.Results: Both 5-FCR and 5-FCC exhibited favorable biocompatibility and safety profiles. VEGF-induced migration of Human umbilical vein endothelial cells (HUVECs) significantly decreased post-5-FCR/5-FCC treatment. Additionally, both complexes suppressed VEGF-induced tube formation in HUVECs. FFA results revealed a significant improvement in retinal exudation in mice. Histological examination unveiled the lesion areas in the 5-FCR and 5-FCC groups showed a significant reduction compared to the control group. Similar outcomes were observed in histological sections of the RPE-choroid-sclera flat mounts.Conclusion: In this study, utilizing the properties of CPP and two anti-VEGF drugs, we successfully synthesized two complexes, 5-FCR and 5-FCC, through a straightforward approach. Effectively delivering the anti-VEGF drugs to the target area in a non-invasive manner, suppressing the progression of laser-induced CNV. This offers a novel approach for the treatment of wet AMD. Keywords: age-related macular degeneration, choroidal neovascularization, cell-penetrating peptide, ranibizumab, conbercept, drug delivery